ICT and Economic Integration on Growth in ASEAN Region: Dynamic Panel GMM Approach - Muhammad Bilal, Ahsin; Jerome, Kueh; Muhammad Asraf, Abdullah (Human Resource Management Academic Research Society, 2021)
Southeast Asian Nations (ASEAN) observed rapid economic growth in the last few decades. This study aims to investigate whether economic integration and information and communication technology (ICT) promotes economic growth in ASEAN. It further examines the role of ICT for economic integration and growth relationship with respect to ICT readiness and usage. The study undertook panel data over 21 years (1997 – 2017) and employed Generalized Method of Moments approach for estimation of results. The results revealed that economic integration and ICT enhance economic growth. Moreover, enhanced ICT stimulates the impact of economic integration on economic growth. The results also confirmed a more substantial effect of ICT readiness on economic growth as compared to ICT usage.